DINAMIKA POLITIK LOKAL DALAM PEMILIHAN ANGGOTABADAN PERMUSYAWARATAN (BAMUS) NAGARI TALU TAHUN 2020 - Riyanda, Riko; Yandri, Lara Indah; Gusrianto, Gusrianto (Ensiklopedia of Journal, 2024)
The BAMUS member selection system cannot be separated from the dynamics in local political developments at the Nagari regional level. The election of BAMUS members also creates a struggle for power, which is common in every round of general elections in Indonesia. Prospective BAMUS members use various methods in the election process to win the election and gain power at the root level. The implementation of the election of BAMUS members in Nagari Talu in 2020 is different from the election of BAMUS members in villages/nagari in general, because it was carried out directly for the first time in West Pasaman. The selection of Bamus members is guided by Minister of Home Affairs Regulation Number 110 of 2016 Challenges to Village Consultative Bodies. The election of Bamus members is carried out democratically with regional representatives and women's representatives. The purpose of this research is to understand the implementation of the BAMUS member election in Nagari Talu and to find out the dynamics of local politics in the 2020 BAMUS Nagari Talu member election. This type of research is descriptive qualitative. The informants in this research were 2 prospective members of Bamus, 1 member of the Bamus Election Committee and 2 traditional leaders. The research results show that the dynamics of local politics in the 2020 BAMUS Nagari Talu member election took the form of protests from several community figures. This cons lies in the aspect of determining the electoral system mechanism. This public figure protested because the mechanism for directly selecting Bamus members had eliminated some of the roles of ninik mamak in the nagari.Keywords: local politics, BAMUS, direct election